Does invader like invader? Feeding preferences of an alien Ponto-Caspian goby towards indigenous and non-indigenous amphipod prey - Dagmara Błońska (Frontiers in Marine Science, 2015)
When non-native species appear in a new ecosystem, it may sufficiently affect native communities i.a. through interactions with native as well as other alien species. The „invasional meltdown“ hypothesis states that the presence of non-indigenous species facilitates the introduction and establishment of the other non-native species. A series of laboratory experiments was conducted to test the occurence of the invasional meltdown phenomenon within the invasive Ponto-Caspian community. Preferences of an alien Ponto-Caspian racer goby, Babka gymnotrachelus, towards amphipod preys of the same origin (Dikerogammarus villosus, Pontogammarus robustoides) or a prey species native to the resident community (Gammarus fossarum) were verified. Additionally, we tested the profitability of native and invasive prey for fish in a growth experiment. Accordingly with the invasional meltdown hypothesis, we hypothesized that the racer goby would prefer Ponto-Caspian amphipods and that prey would be more beneficial than native ones, which should result in higher growth rate. We found that the racer goby always selected the native G. fossarum, regardless of the prey mobility, presence of shelters and waterborne chemical cues. Thus, the fish choice was based on the assessment of prey quality during a direct contact with amphipods. The growth experiment indicated that the racer goby grew better on the native gammarid compared to the Ponto-Caspian species. The outcome of our study does not support the invasional meltdown hypothesis within the goby – gammarids predator prey system, as the non-native prey species were neither prefered nor more profitable food for the alien predator. Thus, we found no evidence for facilitation of establishement between the studied taxa.